2014
DOI: 10.1051/0004-6361/201424466
|View full text |Cite
|
Sign up to set email alerts
|

Pore evolution in interstellar ice analogues

Abstract: Context. The level of porosity of interstellar ices, largely comprised of amorphous solid water (ASW), contains clues about the trapping capacity of other volatile species and determines the surface accessibility that is needed for solid-state reactions to take place. Aims. Our goal is to simulate the growth of amorphous water ice at low temperature (10 K) and to characterise the evolution of the porosity (and the specific surface area) as a function of temperature (from 10 to 120 K). Methods. Kinetic Monte Ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 48 publications
(58 reference statements)
3
41
0
Order By: Relevance
“…One way to account for a SSA increase would be if pore clustering occurs in the ice, leading to larger (internal) pore surface areas in addition to the ice interface to the vacuum. Such a pore clustering was inferred by positron-annihilation spectroscopy [28] and recent kinetic Monte Carlo ice simulations [29]. Our c-ASW ice sample, however, exhibits no pore clustering-the pore shape, the radius (R G ), and periodic spacings between pores all remain constant.…”
supporting
confidence: 50%
“…One way to account for a SSA increase would be if pore clustering occurs in the ice, leading to larger (internal) pore surface areas in addition to the ice interface to the vacuum. Such a pore clustering was inferred by positron-annihilation spectroscopy [28] and recent kinetic Monte Carlo ice simulations [29]. Our c-ASW ice sample, however, exhibits no pore clustering-the pore shape, the radius (R G ), and periodic spacings between pores all remain constant.…”
supporting
confidence: 50%
“…However, it is unclear whether these cavities are closed inside the bulk ASW or interconnected and accessible from the vacuumice interface. In Figure 3 of Raut et al (2007b) and Figure 8 of Cazaux et al (2015), it was hinted that there are closed cavities, but there was no discussion about the connectivity of the cavities. In Figure 12 in this work, it is evident that after CO adsorption, the 3696 cm −1 band always drops to zero, regardless of the annealing temperature.…”
Section: Discussion and Astrophysical Implicationsmentioning
confidence: 99%
“…In Table 2 we observe that these two photodissociation pathways yielding CH 3 and CH 2 radicals are among the slowest steps in the network (r0.1% of the fastest reactions) and therefore determine the rate at which the overall scheme proceeds. 36,45 Compared to photodissociation rates measured in the gas phase, photodissociation rates in the solid phase are in general substantially lower, most likely because of the fast reverse reactions between the dissociation fragments. Previous experimental studies on ices have demonstrated that the photodissociation rates of methane strongly depend on the environment.…”
Section: Discussionmentioning
confidence: 99%